Innate adaptive immune cell dynamics in tonsillar tissues during chronic SIV infection - Shukla, Rajni Kant; Gunasena, Manuja; Reinhold-Larsson, Nicole; Duncan, Michael; Hatharasinghe, Amila; Cray, Samuel; Weragalaarachchi, Krishanthi; Kasturiratna, Dhanuja; Demberg, Thorsten; Liyanage, Namal P. M. (Frontiers in Immunology, 2023)
HIV-infected patients are at higher risk of developing oral mucosal infection and Epstein-Barr virus (EBV)-associated B cell malignancies. However, the potential role of oral immunity in the pathogenesis of oral lesions is unknown. Tonsils are oral-pharyngeal mucosal-associated lymphoid tissues that play an important role in oral mucosal immunity. In this study, we investigated the changes of innate and adaptive immune cells in macaque tonsils during chronic SIV infection. We found significantly higher frequencies of classical monocytes, CD3+CD56+ (NKT-like) cells, CD3 + CD4 + CD8 + (DP), and CD161 + CD4 T cells in tonsils from chronic infected compared to naïve animals. On the contrary, intermediate monocytes and CD3 + CD4 -CD8 -(DN) cells were lower in chronic SIV-infected macaques . We further confirmed a recently described small B-cell subset, NKB cells, were higher during chronic infection. Furthermore, both adaptive and innate cells showed significantly higher TNF-a and cytotoxic marker CD107a, while IL-22 production was significantly reduced in innate and adaptive immune cells in chronic SIV-infected animals. A dramatic reduction of IFN-g production by innate immune cells might indicate enhanced susceptibility to EBV infection and potential transformation of B cells in the tonsils. In summary, our observation shows that the SIV-associated immune responses are distinct in the tonsils compared to other mucosal tissues. Our data extends our understanding of the oral innate immune system during SIV infection and could aid future studies in evaluating the role of tonsillar immune cells during HIV-associated oral mucosal infections.